Aromatic pi-complexation of 1,5-diisocyanonaphthalene with benzene derivatives - Erika Kopcsik; Zoltán Mucsi; Rajmond Schiwert; László Vanyorek; Béla Viskolcz; Miklós Nagy (Scientific Reports)
Abstract Aromatic π-complexes play a significant role in various chemical and biological systems, significantly influencing their physico-chemical and spectroscopic properties. The identification of new compounds capable of π-complex formation is therefore of great interest. The paper investigates the fluorescent properties of 1,5-diisocyanonaphthalene (1,5-DIN) in different aromatic solvents, demonstrating its potential for distinguishing between aromatics based on emission spectra. The resulting spectra can be classified as benzene-, toluene-, and xylene-like types and may be used for the fingerprint identification of benzenes with different electron donating/withdrawing substituents. Comparative studies with related compounds revealed that lower electron density in the naphthalene core favors π-complex formation. The study also found that electron-donating groups in solvents caused more significant redshifts, while electron-withdrawing groups had minimal impact. High-level DFT calculations supported these observations, showing that stronger π-π interactions lead to greater redshifts, particularly in solvents, such as toluene and xylenes. The research suggests that 1,5-DIN’s distinct emission behaviors can be leveraged for compositional analysis of benzene-toluene-xylene (BTX) mixtures, with specific emphasis on the influence of electron density and solvent interactions on the emission properties.